Step-by-step explanation:
Hello there!
Use the formula for the volume of a sphere:
![v=\frac{4}{3} \pi r^1\\V=\frac{4}{3} \pi9\\\\ V=12\pi =37.699111](https://tex.z-dn.net/?f=v%3D%5Cfrac%7B4%7D%7B3%7D%20%5Cpi%20r%5E1%5C%5CV%3D%5Cfrac%7B4%7D%7B3%7D%20%5Cpi9%5C%5C%5C%5C%20V%3D12%5Cpi%20%3D37.699111)
There is your answer!
:)
Answer:
B is correct
Step-by-step explanation:
I think you don't need a calculator here. :) Try to figure out next time!
Lets see together how it gets done
120 180
160 200
200 220
240 240
so the answer is 3 months
<h3>Answer:</h3>
±12 (two answers)
<h3>Explanation:</h3>
Suppose one root is <em>a</em>. Then the other root will be -3<em>a</em>. The product of the two roots is the ratio of the constant coefficient to the leading coefficient:
(<em>a</em>)(-3<em>a</em>) = -27/4
<em>a</em>² = -27/(4·(-3)) = 9/4
<em>a</em> = ±√(9/4) = ±3/2
Then the other root is
-3<em>a</em> = -3(±3/2) = ±9/2 . . . . . . the roots will have opposite signs
We know the opposite of the sum of these roots will be the ratio of the linear term coefficient to the leading coefficient: b/4, so ...
-(a + (-3a)) = b/4
2a = b/4
b = 8a = 8·(±3/2)
b = ±12
_____
<em>Check</em>
For b = 12, the equation factors as ...
4x² +12x -27 = (2x -3)(2x +9) = 0
It has roots -9/2 and +3/2, the ratio of which is -3.
For b = -12, the equation factors as ...
4x² -12x -27 = (2x +3)(2x -9) = 0
It has roots 9/2 and -3/2, the ratio of which is -3.